Four perfect pebbles : a Holocaust story - Perl, Lila.; Lazan, Marion Blumenthal (New York : Avon Camelot, 1999)
The author tells the story of her family's experiences as Jews in Hitler's Germany, tracing their horrifying journey from their home country to Holland and back again, living in refugee, transit, and prison camps, including Bergen-Belson.
Includes bibliographical references (p. 129-130).
Notable/Best Books (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), May 1998.
Book Report, September 1996.
Keywords: Lazan, Marion Blumenthal -- Childhood and youth -- Juvenile literature; Lazan, Marion Blumenthal -- Childhood and youth; Lazan, Marion Blumenthal; Bergen-Belsen (Concentration camp) -- Juvenile literature; Westerbork (Concentration camp) -- Juvenile literature; Bergen-Belsen (Concentration camp); Westerbork (Concentration camp); Bergen-Belsen (Concentration camp); Westerbork (Concentration camp); Holocaust, Jewish (1939-1945) -- Personal narratives -- Juvenile literature; Jews -- Germany -- Biography -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Personal narratives; Jews -- Germany -- Biography; Holocaust, 1939-1945 -- Personal narratives; Jews -- Germany -- Biography; Germany -- Biography -- Juvenile literature